Producing entrepreneurial citizens: Governmentality over and through Hong Kong influencers on Xiaohongshu (Red) - Ju, Ran (Policy and internet, 2022)
Building on Foucault's perspective of governmentality, this article focuses on how influencers in Hong Kong China (HK) operate as agents/mediators of governmentality and how “governmentality” occurs over and through lifestyle influencers as responsible, productive, and self‐disciplined citizen subjects on the Chinese biggest lifestyle sharing platform—Xiaohongshu (Red). By employing a collaboration of walkthrough and ethnographic methods, this article examines how Red's influencer governance, intersecting both HK and Mainland Chinese contexts, guides, trains, and controls influencers and users to become relevant to the practices of entrepreneurial citizenship, and how influencers and their followers act through, rely on and negotiate with the governmental practices and authoritative discourses. These practices and discourses motivate influencers to not only transform themselves into entrepreneurial citizen subjects who could produce individualizing knowledge about self‐care and self‐governance as techniques of disciplining the community, but also expand the key governmental strategies of reconstructing an entrepreneurial identity with their followers on behalf of the government. Although Red is not a mainstream influencer platform in HK, “the governmentality over and through influencers” on Red provides fruitful cases that demonstrate how HK's model of influencer governance is based on the bottom‐up networks through little ways in which management, guidance, and control occur with the active engagement of individual citizens, social organizations, professional associations, and businesses to meet the desired goals of the central and HKSAR government. 摘要 本文分析了小红书（一个中国生活方式分享平台，其愿景是“标记美好生活”，发现并连接多元生活方式）的网红治理术如何对香港网红及用户加以赋权和管控，使其与创业型公民（entrepreneurial citizenship）实践相关。理论框架基于福柯的治理术和“创业自我”（entrepreneurial self’）观点，分析了香港治理术的历史和文化特性，并分析了用于界定“创业公民”的一系列政府实践和话语，这些实践和话语制定了网红治理的重点和模式。本文结合APP漫游法和网络民族志方法，研究了小红书的网红治理（与香港和中国大陆情境交叉）如何使网红向其追随者提供关于自我管理和自我赋权的个性化知识，以及网红和其追随者如何对政府实践和权威话语加以行动、依赖和协商，后者将其视为理想的创业主体。本文论证认为，在更广的治理术框架下能更好地理解香港的网红治理，该框架结合了创业精神和自我管理的新自由主义价值观，以及用于规范社区的社会主义技术科学管理，以实现国家目标。 Resumen Este artículo examina cómo la gubernamentalidad sobre y a través de personas influyentes en Red, una plataforma china para compartir estilos de vida cuya visión es 'inspirar vidas' para descubrir y conectarse con diversos estilos de vida, empodera y controla a personas influyentes y usuarios de Hong Kong para que se vuelvan relevantes para las prácticas de emprendimiento. ciudadanía. El marco teórico se basa en las perspectivas de la gubernamentalidad y el "yo empresarial" de Foucault para examinar las especificidades históricas y culturales de la gubernamentalidad de Hong Kong y las prácticas y discursos gubernamentales para definir a los "ciudadanos emprendedores" que enmarcan su enfoque y modelo de gobernanza influyente. Mediante el empleo de una combinación de métodos etnográficos en línea y tutoriales, este artículo examina cómo la gobernanza de influencers de Red que se cruza con los contextos de Hong Kong y China continental hace que los influencers produzcan conocimiento individualizado sobre la autogestión y el autoempoderamiento para sus seguidores, y cómo los influencers y sus seguidores actuar, apoyarse y negociar con las prácticas gubernamentales y el discurso autoritario posicionándolos como sujetos emprendedores ideales. Este artículo argumenta que la gobernanza de los influencers en Hong Kong podría entenderse mejor dentro del marco más amplio de la gubernamentalidad, que combina el valor neoliberal del espíritu empresarial y la autogestión, y la administración tecnocientífica socialista de disciplinar a la comunidad para lograr los objetivos del estado.